Intravenous Injection of Apolipoprotein A-V Reconstituted High-Density Lipoprotein Decreases Hypertriglyceridemia in apoav−/− Mice and Requires Glycosylphosphatidylinositol-Anchored High-Density Lipoprotein–Binding Protein 1 - Shu, Xiao; Nelbach, Lisa; Weinstein, Michael M.; Burgess, Braydon L.; Beckstead, Jennifer A.; Young, Stephen G.; Ryan, Robert O.; Forte, Trudy M. (Arteriosclerosis, thrombosis, and vascular biology, 2010)
OBJECTIVE—Apolipoprotein A-V (apoA-V), a minor protein associated with lipoproteins, has a major effect on triacylglycerol (TG) metabolism. We investigated whether apoA-V complexed with phospholipid in the form of a reconstituted high-density lipoprotein (rHDL) has potential utility as a therapeutic agent for treatment of hypertriglyceridemia (HTG) when delivered intravenously. METHODS AND RESULTS—Intravenous injection studies were performed in genetically engineered mouse models of severe HTG, including apoav−/− and gpihbp1−/− mice. Administration of apoA-V rHDL to hypertriglyceridemic apoav−/− mice resulted in a 60% reduction in plasma TG concentration after 4 hours. This decline can be attributed to enhanced catabolism/clearance of very-low-density lipoprotein (VLDL), where VLDL TG and cholesterol were reduced ≈60%. ApoA-V that associated with VLDL after injection was also rapidly cleared. Site-specific mutations in the heparin-binding region of apoA-V (amino acids 186 to 227) attenuated apoA-V rHDL TG-lowering activity by 50%, suggesting that this sequence element is required for optimal TG-lowering activity in vivo. Unlike apoav−/− mice, injection of apoA-V rHDL into gpihbp1−/− mice had no effect on plasma TG levels, and apoA-V remained associated with plasma VLDL. CONCLUSION—Intravenously injected apoA-V rHDL significantly lowers plasma TG in an apoA-V deficient mouse model. Its intravenous administration may have therapeutic benefit in human subjects with severe HTG, especially in cases involving apoA-V variants associated with HTG.